Principle of «Observability»: Why Cannot the Theory of the Infinite Universe be Realized? - A N Pavlenko (RUDN Journal of Philosophy, 2009)
The present work demonstrates that all cosmological theories obey an epistemological relation: all steps cosmology makes in the direction of acquiring the status of a natural science are inversely proportional to its steps in the direction of allowing infinite values of cosmological features. An attempt to introduce infinity into the Universe description by the Newtonian model, resulted in the photometric and gravitational paradoxes. To eliminate the paradoxes, relativistic cosmology had to introduce once more the infinite characteristics of the Universe. The same difficulty is typical of the inflationary and chaotic scenarios.